Cardiac problems in Down syndrome. Issue 1 (January 2015) - Marder, Liz; Tulloh, Robert; Pascall, Emma
Abstract: Down syndrome is associated with increased risk of a range of medical problems. One of the major causes of morbidity and mortality is congenital heart disease. Pulmonary arterial hypertension, which occurs more frequently in this population can affect those with or without congenital heart disease. Typical signs and symptoms of these problems may not be present, and screening in the newborn period together with prompt diagnostic assessment and treatment is important to reduce the long term impact of these conditions. Even with early treatment, many children with Down syndrome will have ongoing complications and pulmonary arterial hypertension. Close surveillance and active management throughout childhood and into adulthood is needed in order to optimise quality of life long term.